Treatment of jaw fracture due to firearm injury as a result of domestic violence (Research, Society and Development, 2021)
The increase in the rates of interpersonal violence has generated a great impact on world society, mainly due to the number of victims affected by injuries caused by fire gun projectiles. Taking into account the severity of this type of injury, the need for surgical intervention, and the significant increase in victimized women, the importance of knowledge, on the part of the maxillofacial surgeon, of the technical surgical procedure, and the welcoming of the victim is highlighted. This work aims to highlight the social problem involving feminicide and report descriptively a case, in which the patient was the victim of attempted homicide, thus requiring surgical intervention to reduce and fix a comminuted fracture in the mandibular region. The patient is 8 years postoperative, showing osteosynthesis and occlusion stability, normally performing all functions of the stomatognathic system. Thus showing the success of the chosen surgical approach.